PERSEPSI MAHASISWA TERHADAP KOMPETENSI DOSEN PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Hodsay, Zahruddin (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractThe papers are the Studentsâ Perception on Lecturer Competence at Accounting Education Study Program FKIP PGRI University Palembang. This is a descriptive research. The population of this research are all the 7th grade students of Accounting Education Study Program FKIP PGRI University Palembang in academic year of 2012/2013.Â Purposive sampling technique was applied in choosing the 200 out 680 students as sample of this study. Questionnaire and documentation were used in collecting data which was analyzed qualitatively through descriptive and percentage analysis. The result of this study showed that 93% (36 out of 39 lecturers) have pedagogic competence while 7% (3 lecturers) had not had or did not have it. In addition, 92% (35 lecturers) have professional competence while 8% (4 lecturers) had not had or did not have it. Â Keywords: Perception, Competence, Deskriptive, Pedagogic Competence, professional competence